2014
DOI: 10.3109/09638288.2014.892640
|View full text |Cite
|
Sign up to set email alerts
|

“This is not just a little accident”: a qualitative understanding of paediatric burns from the perspective of parents

Abstract: Findings from this research will allow health professionals to optimise a holistic clinical service from a consumer's perspective at all stages of the burn journey. These research conclusions could be used for the development of protocols to underpin a comprehensive information and social support management plan for families that would complement and support the surgical, medical and therapeutic treatment plan, providing direction for comprehensive service delivery. Implications for Rehabilitation Health profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 21 publications
(39 reference statements)
7
62
0
16
Order By: Relevance
“…A burn trauma affects several dimensions of health of the injured child, and also has a great impact on the family as a whole for a long period of time thereafter [1,2]. Parents are very much involved in the care of the child, both during the hospital stay and after discharge, and their views are essential for improvement of pediatric burn care.…”
Section: Introductionmentioning
confidence: 99%
“…A burn trauma affects several dimensions of health of the injured child, and also has a great impact on the family as a whole for a long period of time thereafter [1,2]. Parents are very much involved in the care of the child, both during the hospital stay and after discharge, and their views are essential for improvement of pediatric burn care.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly the burn injury can result in the typical roles that parents have in the household changing, for example one parent may start to take responsibility for more aspects of the housework or childcare and these changing roles can sometimes increase tensions between partners (Griffiths et al, in preparation;Horridge et al, 2010). Parents may feel overwhelmed with guilt over their child's injury and this can place further pressure on the martial relationship (McGarry et al, 2014).…”
Section: How Can Parents Themselves Be Affected When Supporting Theirmentioning
confidence: 99%
“…Particularly in the early weeks after the injury, these experiences can be distressing and painful for some children, and for parents to witness their child in pain can further increase parents' stress (McGarry et al, 2014).…”
Section: How Can Parents Themselves Be Affected When Supporting Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents and caregivers have been demonstrated to use negative coping reactions such as blame when caring for a burn-injured child and experience feelings of guilt [22]. Accordingly, research has also shown that a child's psychosocial recovery can be impacted on by parents' responses to the burn event [23].…”
Section: Experiencementioning
confidence: 99%